A different interpretation of the annual and semiannual anomalies on the magnetic activity over the Earth - Azpilicueta, Francisco Javier (2012)
The H component of the magnetic field measured at the terrestrial surface presents several periodic signals caused by changes in the ring current that flows within the terrestrial magnetosphere. One of the most important of them is associated to the phenomenon known as the Semiannual Anomaly which produces two significant minima during the equinoxes. This phenomenon is global, i.e., every observatory registers a similar effect independently of the hemisphere where it is located. A second important signal is due to the phenomenon known as the Annual Anomaly that produces significant different values for solstices, with a particular feature: the effect depends on the hemisphere where the observatory is located, with maximum during local summer. In spite of the time since their discoveries (more than a hundred years ago) the physical processes behind them are still open to discussion. In this work we present a new physical interpretation for the combined effects of both anomalies. The main concept developed is that along the year the shape of the magnetospheric cavities within which the ring current flows is deformed according to the geometric configuration between the solar wind and the magnetosphere.